2012
DOI: 10.3126/kumj.v9i4.6336
|View full text |Cite
|
Sign up to set email alerts
|

Use of Gabapentin, Esmolol or Their Combination to Attenuate Haemodynamic Response to Laryngoscopy and Intubation

Abstract: Background

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
13
0
1
Order By: Relevance
“…In the study by Iftikhar they reported a significant difference for heart rate in Gabapentin and placebo group. 20 There is yet an undocumented but strong observation that population in our part of the world is very sensitive to the sedative effects of gabapentin. It is worthwhile noting that studies by Shirpa, Fassoulaki and Tahera exclude nasotracheal intubation in patients undergoing oral and maxillofacial surgeries and it appears that pre-operative gabapentin blunts the heamodynamic response to nasotracheal intubation as well as in endotracheal intubation.…”
Section: Resultsmentioning
confidence: 99%
“…In the study by Iftikhar they reported a significant difference for heart rate in Gabapentin and placebo group. 20 There is yet an undocumented but strong observation that population in our part of the world is very sensitive to the sedative effects of gabapentin. It is worthwhile noting that studies by Shirpa, Fassoulaki and Tahera exclude nasotracheal intubation in patients undergoing oral and maxillofacial surgeries and it appears that pre-operative gabapentin blunts the heamodynamic response to nasotracheal intubation as well as in endotracheal intubation.…”
Section: Resultsmentioning
confidence: 99%
“…3). At five minutes, the analysis included 21 studies [21][22][23][24]26,[28][29][30][32][33][34][35][36][37][38][39]41,[43][44][45]47 with 1,350 participants where the aggregated effect estimate showed an attenuated rise with gabapentin (MD -9 mmHg; 95% CI, -13 to -5; low quality). At ten minutes, the analysis included 18 studies [21][22][23]26,28,30,[32][33][34][35][36][37][38][39]41,43,44,47 with 1,244 participants where the aggregated effect estimate showed an attenuated rise with gabapentin (MD, -8 mmHg; 95% CI, -11 to -5; low quality).…”
Section: Secondary Outcomesmentioning
confidence: 99%
“…One study 45 compared gabapentin with a beta blocker (esmolol). The only difference in hemodynamic variables was a higher HR at one minute in the gabapentin group when compared with the esmolol group (MD, 13 beatsÁmin -1 ; 95% CI, 4 to 21).…”
Section: Gabapentin Vs Fentanyl Clonidine or Beta Blockersmentioning
confidence: 99%
“…Obat-obat tersebut masing-masing memiliki keterbatasan sehingga terus dikembangkan penelitian untuk mendapatkan obat adjuvan yang mempunyai efek analgetik serta dapat meningkatkan kualitas analgesia opioid, mengurangi kebutuhan opioid, mencegah atau mengurangi toleransi opioid, mengurangi level kecemasan, serta mempunyai batas keamanan yang lebar. [1][2][3][4] Gabapentin secara kimiawi larut dalam air, memiliki rasa pahit, struktur berbentuk kristal putih mirip gugus gamma aminobutyric acid atau GABA dengan cincin cyclohexane. Aksi yang paling penting gabapentin adalah ikatan subunit α 2 δ voltage dependent calcium channels.…”
Section: Pendahuluanunclassified